Utilization of LGBT-Specific clinics and providers across three cohorts of lesbian, gay, and bisexual people in the United States - Alexander J. Martos; Adam Fingerhut; Patrick A. Wilson; Ilan H. Meyer (Elsevier, 2019)
Lesbian, gay, and bisexual (LGB) people navigate issues of stigma, discrimination, structural barriers, and a history of medical mistrust when seeking healthcare services. Lesbian, gay, bisexual, and transgender (LGBT)-specific clinics and providers offer alternative spaces where these issues may be avoided, but limited research is available on how LGB people utilize these resources. The current study analyzes data from a nationally-representative survey of 1534 LGB people across three age cohorts. Gender, sexual identity, income, proximity to LGBT community health centers, perceived health status, and the total number of lifetime diagnoses are each associated with past utilization of LGBT-specific clinics and providers; interest in future utilization is associated with sexual identity, race/ethnicity, several psychosocial factors, income, a usual source of care, and mental distress. We conclude that LGBT-specific clinics and providers represent an important piece of the healthcare landscape for LGB people but access remains an important barrier to utilization.